Preservatives as important etiologic factors of allergic contact dermatitis - Beata Kręcisz; Dorota Chomiczewska-Skóra; Marta Kieć-Świerczyńska (Nofer Institute of Occupational Medicine, 2015)
Background: Preservatives present in cosmetics and other industrial products can cause allergic contact dermatitis. The aim of the study was to assess the frequency of allergy to selected preservatives in consecutive patients examined due to contact dermatitis in the Nofer Institute of Occupational Medicine, Łódź, and to establish whether individuals sensitized to formaldehyde react simultaneously to formaldehyde releasers. Material and Methods: A group of 405 patients (308 females and 97 males) was examined in 2011-2013. In all participants patch tests with a series of 13 preservatives (paraben mix, formaldehyde, Quaternium 15, chloromethylisothiazolinone/methylisothiazolinone mix, methyldibromoglutaronitrile, diazolidinyl urea, imidazolidinyl urea, DMDM hydantoin, 2-bromo-2-nitropropane-1,3-diol, iodopropynyl butylcarbamate, benzalkonium chloride, sodium metabisulfite, produced by Chemotechnique Diagnostics, Sweden) were performed. Results: Of the 405 patients 74 (including 52 females) showed positive results of patch tests. Contact allergy to at least 1 preservative was noted in 47 (11.6%) patients, including 34 (11%) females and 13 (13.4%) males. Methylisothiazolinone proved to be the most frequent sensitizer - 4.7% (5.2% females, 3.1% males) while parabens, 2-bromo-2-nitropropane-1,3-diol and imidazolidinyl urea (0.2%) were found to be the least frequent. Fourteen (3.4%) participants, 10 women and 4 men, were allergic to formaldehyde and/or formaldehyde releasers. In 11 (78.6%) of them monovalent hypersensitivity was observed. In 13 (3.2% of the examined group) patients allergy to preservatives might have been of occupational origin. Conclusions: Preservatives, particularly isothiazolinones, are significant causal factors of allergic contact dermatitis, including occupational cases. Individuals sensitized to formaldehyde may react simultaneously to formaldehyde releasers, however, such reactions are relatively rare. Med Pr 2015;66(3):327-332